Linking components of social media usage to psychological distress: integrating the situational theory of problem-solving and social capital theory - Tian, Wei; De Costa, Feroz; Abdul Rahiman, Amir Rizaan; Roh, Taewoo (Elsevier Ltd, 2025)
Despite extensive research on psychological distress, studies that examine how social media usage impacts psychological distress are notably missing. This study employs the lenses of the situational theory of problem-solving and social capital theory to examine the relationship between social media usage and psychological distress. Our hypotheses propose that social media activities play a mediating role in the relationship between social media usage and psychological distress, while media skepticism and interpersonal injustice act as moderating factors. A structured questionnaire was developed and distributed to social media users in five major Chinese cities: Shenzhen, Guangzhou, Dongguan, Zhuhai, and Shantou. Non-probability convenience sampling and a two-wave research design were employed to collect data from 866 social media users. The results indicated a positive association between social media usage and psychological distress. Notably, social media activities were a positively significant mediator of this relationship. However, the moderating effect of media skepticism was non-significant, while interpersonal injustice reduces the impact of social media usage on psychological distress. The relationship between constraint recognition and psychological distress was not significant. These findings lead to practical insights for efficiently controlling social media participation and online behaviors, while also considering how interpersonal unfairness and other factors influence users' emotional distress levels.